Structure and distribution of gynaecological diseases for girls and teenage girls in the Zaporizhzhia area - N. V. Avramenko; O. V. Kabachenko; T. O. Tsaruk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Background. In recent years the question of gynecological diseases in women and teenage girls becomes more and more relevance. Girls of pubertal age should become mothers of new generation, but the health of adolescents continues to deteriorate.